Renewable energy and the environment - Isalāma, Moḥ. Rabiula; Roy, Naruttam Kumar; Rahman, Saifur (Renewable energy sources & energy storage, 2018)
This book discusses a number of important topical technical and non-technical issues related to the global energy, environment and socio-economic developments for professionals and students directly and indirectly involved in the relevant fields. It shows how renewable energy offers solutions to mitigate energy demand and helps achieve a clean environment, and also addresses the lack of a clear vision in the development of technology and a policy to reach the mandatory global renewable energy targets to reduce greenhouse gas emissions and stimulate socio-economic development. The book is structured in such a way that it provides a consistent compilation of fundamental theories, a compendium of current research and development activities as well as new directions to overcome critical limitations; future technologies for power grids and their control, stability and reliability are also presented. - Resumé vydavatel